Native T(1) reference values for nonischemic cardiomyopathies and populations with increased cardiovascular risk: A systematic review and meta‐analysis - van den Boomen, Maaike (J Magn Reson Imaging, 2017)
BACKGROUND: Although cardiac MR and T(1) mapping are increasingly used to diagnose diffuse fibrosis based cardiac diseases, studies reporting T(1) values in healthy and diseased myocardium, particular in nonischemic cardiomyopathies (NICM) and populations with increased cardiovascular risk, seem contradictory. PURPOSE: To determine the range of native myocardial T(1) value ranges in patients with NICM and populations with increased cardiovascular risk. STUDY TYPE: Systemic review and meta‐analysis. POPULATION: Patients with NICM, including hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM), and patients with myocarditis (MC), iron overload, amyloidosis, Fabry disease, and populations with hypertension (HT), diabetes mellitus (DM), and obesity. FIELD STRENGTH/SEQUENCE: (Shortened) modified Look–Locker inversion‐recovery MR sequence at 1.5 or 3T. ASSESSMENT: PubMed and Embase were searched following the PRISMA guidelines. STATISTICAL TESTS: The summary of standard mean difference (SMD) between the diseased and a healthy control populations was generated using a random‐effects model in combination with meta‐regression analysis. RESULTS: The SMD for HCM, DCM, and MC patients were significantly increased (1.41, 1.48, and 1.96, respectively, P < 0.01) compared with healthy controls. The SMD for HT patients with and without left‐ventricle hypertrophy (LVH) together was significantly increased (0.19, P = 0.04), while for HT patients without LVH the SMD was zero (0.03, P = 0.52). The number of studies on amyloidosis, iron overload, Fabry disease, and HT patients with LVH did not meet the requirement to perform a meta‐analysis. However, most studies reported a significantly increased T(1) for amyloidosis and HT patients with LVH and a significant decreased T(1) for iron overload and Fabry disease patients. DATA CONCLUSIONS: Native T(1) mapping by using an (Sh)MOLLI sequence can potentially assess myocardial changes in HCM, DCM, MC, iron overload, amyloidosis, and Fabry disease compared to controls. In addition, it can help to diagnose left‐ventricular remodeling in HT patients. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:891–912.